Exercise heart rate during training and competitive matches in elite soccer: more questions than answers - Diouron, I.; Leduc, C.; Escudier, G.; Perrey, S. (Sports, 2025)
Monitoring the training load of elite soccer players is a common practice for clubs. However, limited information exists about the internal load experienced by elite soccer players. The heart rate (HR) exposure of 51 French elite soccer players was monitored using conductive vests incorporating ECG bands during two consecutive seasons using a three-zone intensity model. HR exposure was broken down into volume (i.e., total time in the three zones) and intensity (i.e., relative time in the three zones). The effect of playing position, as well as the period (monthly or daily), was assessed. Regarding seasonal exposure, a significant difference was observed between key periods of the season (i.e., preseason, in season, end-of-season) for both volume and intensity (p < 0.05). Noteworthily, monthly HR exposure was relatively constant across competitive period. For weekly exposure, a significant difference in HR volume and intensity was observed between matches and training sessions (p < 0.001) potentially highlighting gaps in players` readiness. Note that there were small variations in terms of HR exposure between the three first training days (p < 0.05), especially for time and relative time over 90% of maximal HR (not significant). This study not only provides insight into typical HR exposure in elite football but also questions the current training periodisation.